Proportionality in the CJEU’s Internet Copyright Case Law: Invasive or Resilient? - Tuomas Mylly (Kluwer Law International, 2022)
The chapter analyses how the CJEU operates with fundamental rights proportionality in the context of copyright and the information society. It theorizes the underlying issues, especially through the notions of incommensurability, rights inflation and externalities. The argument of the chapter is that the CJEU resorts to fundamental rights proportionality stricto sensu excessively, in the absence of an adequate method. Its judgments fill in gaps in Union law with inflated rights, hence expanding the scope of EU law. Disturbingly, it does not seem to realize the structuring effects of its rulings on the digital society. The cases may be about private law relations and rights on the surface level, but through their effects, they are more about judicially regulating the digital society through rights proportionality. Rather than reflecting a conscious agenda on the part of the CJEU, the development is evolutive and could be seen as part of two related global megatrends: power shifting to the judiciary and balancing as the paradigmatic judicial method of ourt ime. In the EU, these trends are strengthened by the already traditionally creative role of the CJEU in developing Union law, as well as the more recent constitutional elevation of the Charter of Fundamental Rights of the European Union.
General Principles of EU Law and the EU Digital Order